2016
DOI: 10.21082/jhort.v24n2.2014.p171-178
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Teknik Deteksi Fusarium Patogen Pada Umbi Benih Bawang Merah (Allium ascalonicum) di Laboratorium

Abstract: Naskah diterima tanggal 7 Maret 2014 dan disetujui untuk diterbitkan tanggal 5 Juni 2014 ABSTRAK. Penyakit layu fusarium yang disebabkan oleh Fusarium oxysporum merupakan salah satu penyakit penting pada bawang merah (Allium ascalonicum). Sebagian besar petani menggunakan umbi sebagai benih dan diketahui bahwa beberapa patogen dapat terbawa oleh benih seperti Fusarium oxysporum. Oleh karena itu diperlukan pengujian kesehatan benih untuk mencegah penyebaran penyakit tersebut. Salah satu metode sederhana dan efe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 9 publications
0
11
0
5
Order By: Relevance
“…is a soilborne pathogen where the initial attack of this pathogen infects the roots or leaves contact directly to the soil surface. Fadhilah et al (2014) reported that Fusarium-affected plants showed disturbed root growth. The LAI is the ratio of the overall leaf area to the land area.…”
Section: Resultsmentioning
confidence: 99%
“…is a soilborne pathogen where the initial attack of this pathogen infects the roots or leaves contact directly to the soil surface. Fadhilah et al (2014) reported that Fusarium-affected plants showed disturbed root growth. The LAI is the ratio of the overall leaf area to the land area.…”
Section: Resultsmentioning
confidence: 99%
“…Fusarium wilt caused by Fusarium oxysporum f.sp. cepae (Wiyatiningsih, 2002;Fadhilah, 2014) is a soil borne fungus which can attrack almost at all stages of plant growth (Cramer, 2000). Control of this disease is usually done by pesticides, sanitation, and crop rotation.…”
Section: Introductionmentioning
confidence: 99%
“…Nugroho et al (2011) specified that high intensity of basal plate rot disease can reduce the bulb weight. According to Fadhilah et al (2014), FOCe infection inhibits shallot growth and causes yield losses as the bulbs are rotting. In this study, there was no variety categorized as susceptible.…”
Section: Resultsmentioning
confidence: 99%